Transplant oncology and anti-cancer immunosuppressants - Kong, Dejun; Duan, Jinliang; Chen, Shaofeng; Wang, Zhenglu; Ren, Jiashu; Lu, Jianing; Chen, Tao; Song, Zhuolun; Wu, Di; Chang, Yuan; Yin, Zhongqian; Shen, Zhongyang; et al. (Frontiers in Immunology, 2025)
Organ transplantation is a life-saving intervention that enhances the quality of life for patients with end-stage organ failure. However, long-term immunosuppressive therapy is required to prevent allogeneic graft rejection, which inadvertently elevates the risk of post-transplant malignancies, especially for liver transplant recipients with a prior history of liver cancer. In response, the emerging field of transplant oncology integrates principles from oncology and immunology to improve outcomes for patients at high risk of tumor occurrence or recurrence following transplantation. Therefore, it is of substantial clinical significance to develop immunosuppressants that possess both immunosuppressive and anti-tumor properties. For instance, mTOR inhibitors demonstrate anti-tumor effects among antimetabolite immunosuppressive drugs, and recent studies indicate that capecitabine, an antimetabolite chemotherapeutic, may also exhibit immunosuppressive activity in the clinic for liver transplants suffering from hepatocellular carcinoma. This review systematically explores potential immunosuppressants with dual anti-tumor and immunosuppressive effects to support the management of transplant patients at elevated risk of tumor occurrence or recurrence.